A case of extraskeletal chondroma of the temporomandibular joint capsule. Issue 5 (September 2015) - Nojima, Junya; Okubo, Masahiko; Hayashi, Naoki; Sano, Yoshie; Enoki, Yuichiro; Fukushima, Yosuke; Sato, Tsuyoshi; Yoda, Tetsuya
Abstract: Extraskeletal chondromas are rare benign cartilaginous tumors. Clinically, these tumors are most frequently found in the hands and feet. However, it is extremely rare for them to develop in the oral and maxillofacial regions. We present the case of a 50-year-old man with a tumor lesion of the temporomandibular joint capsule, which is a site that has not been described previously. Based on the physical examination and imaging study, the tumor was located in the joint capsule, and it was locally excised and pathologically diagnosed as extraskeletal chondroma. Postoperatively, residual disability and tumor recurrence were not observed.